E-government maturity models: more of the same? - Kawashita, Ilka (2020)
As e-government initiatives progressed, several models for measuring e-government maturity were proposed. Many are stage models based on the Capability Maturity Model (CMM) in which e-government maturity is conceptualized as stages of growth that evolve over time. The paper aims to investigate if e-government stage maturity models measure the use and usefulness of egovernment. A meta-synthesis technique was used to compare and contrast 11 meta-models (models derived from other models), at the stage level, for their perspectives, concepts, metaphors, and their similarities and differences. We found that although models use different names and metaphors for analogous concepts, similarities exist among them, and individual stages overlap. Results show two gaps in research regarding the assessment of the actual use and usefulness of e-government. First, meta-models primarily assess the supply-side and operational/technology and citizen/service perspectives. Second, the use and usefulness of e-government are not addressed.